Population Size, Non-Breeding Fraction, and Productivity in a Large Urban Population of Burrowing Parrots (Cyanoliseus patagonus) - Lera, Daiana Noelia (2023)
Psittaciformes are one of the bird orders with the highest number of threatened species and the most marked declining population trends. At present, the lack of information on the population size, reproductive fraction, and productivity of most parrot populations makes it difficult to design effective conservation actions. In this study, we monitored a population of Burrowing Parrots (Cyanoliseus patagonus) breeding in urbanized habitats in the southwest of Buenos Aires province, Argentina. Every December and February from 2018 to 2023, we counted the individuals arriving at a single communal roost, located in the main park of Bahía Blanca city, which gathers all the parrots breeding in 18–22 colonies within a radius of 20 km. Censuses were conducted before (December) and immediately after the incorporation of juveniles into the flocks (February). Breeding pairs were also counted annually in the colonies, and the average annual productivity and the proportion of juveniles were estimated from surveys in pre-roosting and feeding areas in February. The non-breeding fraction approached half of the population with no statistically significant differences among years (range: 37–53%), and the breeding population showed little annual variation, with a minimum of 1363 and a maximum of 1612 breeding pairs. The proportion of juveniles in the flocks and the estimated productivity showed larger variations among breeding seasons. Our results add insight to the scarce information available on the breeding-to-non-breeding-population ratios in parrots, and birds in general, and show key breeding parameters for a species that is thriving well in urban habitats.